STATUS HUKUM WAJIB PAJAK WARGA NEGARA INDONESIA YANG TINGGAL MENETAP DI LUAR NEGERI - David Setiyawan (Fakultas Hukum Universitas Narotama, 2020)
Indonesian citizens who reside abroad have dual tax resident issues, therefore has a double taxation on tax administration and has additional tax administration burden. This is happened since before settling abroad, the Indonesian citizen has a Tax ID (NPWP) in Indonesia and when settling abroad, is given the status of a taxpayer in the country concerned. The existence of an international taxation concept regarding the conflict of tax resident status raises uncertainty over which state taxpayer status is the citizen. Basically, the concept of international taxation and Indonesian taxation adheres to the principle of existence to determine one's taxpayer status. Thus, as long as it can be proven by official documents related to the existence of the Indonesian Citizens who have settled abroad, then the subjective tax obligations of the Indonesian citizen should have ended. Therefore, the Indonesian citizen can submit revocation of the Taxpayer Identification Number (NPWP) and if rejected, he can file a legal claim for the claim.